USING UML DIAGRAMS FOR THE TECHNOLOGICAL PROCESS IN PRODUCTION - SAMCHUK, LUDMILA; POVSTIANA, YULIA; LISHCHYNA, NATALIIA; KLYMENKO, ARTEM (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article uses the unified UML modeling language to visualize production elements. To show some of the advantages of the proposed approach, the main components of the production system are defined: technological machines, operators, materials, products and the production process. A class diagram is used to represent the components. Defined attributes and methods of each class: attributes and methods to each class that define its properties and behavior. The Machine class can have attributes such as machine ID and Destination, and methods such as start() and stop(). Relationships between classes are established: association, aggregation, and composition to represent relationships between classes. The Production Process class can have an aggregation relationship with the Machine class, indicating that the production process consists of multiple machines. This work contains UML diagrams and description tables that make it possible to structure the activity of the technological process in production. The technological process of manufacturing products is shown, which is presented in detail on the state diagram.